¿Un mismo ceremonial para dos dinastías? Las entradas reales de Martín el Humano (1397) y Fernando I (1412) en Barcelona - Raufast Chico, Miguel (En la España Medieval, 2007)
Based on a comparative analysis of royal entries into the city of Barcelona by kings Martin the Human (1397) and Ferdinand I (1412), this study aims to show to what extent the ceremonial inherent in this kind of ritual event was essentially determined by a tradition of reception practices unique to the city, rather than by the monarch’s will or by the fact that the kings belonged to different dynasties. The study offers a dynamic image of the royal entry, rather than a dramatized one, by placing it into a larger analytical framework where its less visible features may emerge and more obvious ones can be redefined.